Handbook of research on design, control, and modeling of swarm robotics - Tan, Ying (Advances in computational intelligence and robotics (ACIR), 2016)
This book is a collection of the most important research achievements in swarm robotics thus far, covering the growing areas of design, control, and modeling of swarm robotics.